Modification structure of chalcone compounds and synthesis of their nickel(II) and copper (II) complexes - Chua, Rose Siaw Chin (Universiti Malaysia Sarawak, UNIMAS, 2012)
Four bis-chalcone compounds with different para- or ortho-substituted were synthesised by Claisen-Schmidt condensation of terephthaladehyde and para- or ortho-substituted Racetophenone under base condition. These bis-chalcone were used as the ligands for synthesising their nickel(II) and copper(II) complexes. All the synthesised bis-chalcones and their complexes were characterised by IR, 1H NMR, and UV-Vis spectroscopy. The spectra data showed that the introducing of different para- or ortho-substituents on the aromatic rings have a great influenced on the carbonyl group, vinylic protons, and charge transfer within the whole molecule of bis-chalcones. The comparison of the IR spectra of the bis-chalcones and their metal complexes indicated that only the bis-chalcone with the hydroxyl substituent was successfully coordinated to nickel(II) ion in 1:1 molar ratio to form the complex through the oxygen atoms of the carbonyl and phenolic group.